Religious Moderation and the Exegesis of Qur’anic Verses on Tolerance: A Comparative Study of Tafsir Al-Misbah and Tafsir Al-Azhar and Its Relevance to Indonesia’s National Life - Sudarmadi Putra; Rakhmad Agung Hidayatullah (Attractive : Innovative Education Journal, 2026)
Religious moderation is a strategic need in a pluralistic Indonesian society, especially to strengthen relations between religious communities without blurring the boundaries of faith. This study aims to analyze and compare interpretations of tolerance verses in Tafsir Al-Misbah and Tafsir Al-Azhar, and to assess their relevance to the lives of Indonesian nationals. The method used is qualitative, descriptive-analytical with a comparative approach, through the study of texts on the interpretation of tolerance verses and analysis of the methodology, socio-historical context, and social implications of each mufasir. The results of the study show that both interpretations affirm the principles of respect for differences, prohibition of religious coercion, and justice in social relations; however, they differ in emphasis and orientation. Tafsir Al-Misbah tends to be contextual, linking the verse’s meaning to the dynamics of plurality and modern citizenship. At the same time, Tafsir Al-Azhar is more historical-da’wah, with an emphasis on the ummah’s experience and the ethics of interfaith association. The contribution of this research enriches the study of the interpretation of the archipelago by comparative mapping of the concept of tolerance as the basis of religious moderation, and it provides practical implications for education, da’wah, and strengthening harmony within the national framework.